2020
DOI: 10.3390/rs12061017
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of PROBA-V LAI, fAPAR and fCOVER Collection 300 m Products of Copernicus Global Land Service

Abstract: The Copernicus Global Land Service (CGLS) provides global time series of leaf area index (LAI), fraction of absorbed photosynthetically active radiation (fAPAR) and fraction of vegetation cover (fCOVER) data at a resolution of 300 m and a frequency of 10 days. We performed a quality assessment and validation of Version 1 Collection 300 m products that were consistent with the guidelines of the Land Product Validation (LPV) subgroup of the Committee on Earth Observation System (CEOS) Working Group on Calibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…This result is consistent with two validation studies which both showed MODIS LAI had the poorest performance for the evergreen forests in the south of China [80,81]. The MODIS LAI values for tropical evergreen forests are severely impacted by atmospheric conditions, especially clouds during the growing season (around 42% data are influenced by the cloud in this study, Figure S8), which lead to strong noise in the input reflectance data and affect the retrieval [78]. Additionally, the reflectance saturation usually happened in dense canopies and the main algorithm is sensitive to uncertainties in atmospheric correction, particularly when red and NIR BRFs are saturated [82,83].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with two validation studies which both showed MODIS LAI had the poorest performance for the evergreen forests in the south of China [80,81]. The MODIS LAI values for tropical evergreen forests are severely impacted by atmospheric conditions, especially clouds during the growing season (around 42% data are influenced by the cloud in this study, Figure S8), which lead to strong noise in the input reflectance data and affect the retrieval [78]. Additionally, the reflectance saturation usually happened in dense canopies and the main algorithm is sensitive to uncertainties in atmospheric correction, particularly when red and NIR BRFs are saturated [82,83].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the core operational algorithm (neural network techniques), data filtering and smoothing processes are similar for these two products. There are differences in the method used for temporal compositing, where temporal smoothing and gap filling using a climatology are used for GEOV2 1 km and interpolation applied in GEOV3 300 m) [78]. Differences in the applied gap-filling approach between these two products do not impact our conclusion that resolution is the primary driver of performance improvement at 300 m relative to 1 km, as all gap-filled and interpolated retrievals were removed in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Figure 4 shows the global distribution of the sampling used in this study. The product intercomparison is evaluated over a 725-site land validation network (LANDVAL) of sites [67], which is designed to globally represent the variability of land surface types, and was used as the spatial sampling to evaluate these criteria. This network also includes 20 well-known desert calibration sites [26] for the precision evaluation, due to their high temporal stability.…”
Section: Validation Methodsmentioning
confidence: 99%
“…LAI, fAPAR and fCover products from lowresolution sensors such as MODIS, MERIS, SPOT-VEGETATION and PROBA-V have been routinely generated and made available free of charge to the public (Bacour et al, 2006;Baret et al, 2007;Fuster et al, 2020;Myneni et al, 2002). Recent work by Clevers et al (2017), Delloye et al (2018) and Pan et al (2019) has shown the potential of Sentinel-2 data for retrieving LAI for crops.…”
Section: Introductionmentioning
confidence: 99%